The Design of The Piping System to Produce Laminar Fountains in Mechanical Pool - PUTRA TJIOE (NIM : 13114108), ERIC
In this era of globalization, modern aged people live in an enviroment where energy plays an important role. Oil, gas, and water are major participants in the supply of energy, and those fluilds are trasported by the piping system. Laminar flow device is one of piping systems components that have function to change turbulent flow into laminar flow. One of the applications is to produce laminar fountain that function as aesthetics. Many factors have to be considered in designing the piping system process to achieve optimum results. Thus performing analysis and calculation of the piping system design from mechanic of fluid field is a necessity to obtain appropiate fountain flow including determination of optimal diameter of every piping segment to obtain minimun total cost and determination appropriate pump specification. The Optimum diameters are 2” for the second segment, 2” for the third segment, 1-1/4” for the fourth segment and ¾” for the fifth segment. The piping system needs a pump that can afford head as 2,58 m and flowrate 1,329x10-3 m3/s so that Grundfos CME 10-1 is choosen and is operated at speed of 1378 RPM.